Antiallodynic action of phosphodiesterase inhibitors in a mouse model of peripheral nerve injury. (1st March 2022) - Megat, Salim; Hugel, Sylvain; Journée, Sarah H.; Bohren, Yohann; Lacaud, Adrien; Lelièvre, Vincent; Doridot, Stéphane; Villa, Pascal; Bourguignon, Jean-Jacques; Salvat, Eric; Schlichter, Remy; Freund-Mercier, Marie-José; et al.
Abstract: Neuropathic pain arises as a consequence of a lesion or disease affecting the somatosensory nervous system. It is accompanied by neuronal and non-neuronal alterations, including alterations in intracellular second messenger pathways. Cellular levels of 3′, 5′-cyclic adenosine monophosphate (cAMP) and 3′, 5′-cyclic guanosine monophosphate (cGMP) are regulated by phosphodiesterase (PDE) enzymes. Here, we studied the impact of PDE inhibitors (PDEi) in a mouse model of peripheral nerve injury induced by placing a cuff around the main branch of the sciatic nerve. Mechanical hypersensitivity, evaluated using von Frey filaments, was relieved by sustained treatment with the non-selective PDEi theophylline and ibudilast (AV-411), with PDE4i rolipram, etazolate and YM-976, and with PDE5i sildenafil, zaprinast and MY-5445, but not by treatments with PDE1i vinpocetine, PDE2i EHNA or PDE3i milrinone. Using pharmacological and knock-out approaches, we show a preferential implication of delta opioid receptors in the action of the PDE4i rolipram and of both mu and delta opioid receptors in the action of the PDE5i sildenafil. Calcium imaging highlighted a preferential action of rolipram on dorsal root ganglia non-neuronal cells, through PDE4B and PDE4D inhibition. Rolipram had anti-neuroimmune action, as shown by its impact on levels of the pro-inflammatory cytokine tumor necrosis factor-α (TNFα) in the dorsal root ganglia of mice with peripheral nerve injury, as well as in human peripheral blood mononuclear cells (PBMCs) stimulated with lipopolysaccharides. This study suggests that PDEs, especially PDE4 and 5, may be targets of interest in the treatment of neuropathic pain. This article is part of the Special Issue on 'Advances in mechanisms and therapeutic targets relevant to pain'. Highlights: PDE4i and PDE5i alleviate mechanical allodynia induced by peripheral nerve injury. The opioid system is necessary for PDEi action. Rolipram acts on non-neuronal cells in dorsal root ganglia. Rolipram decreases tumor necrosis factor-α expression.